THE IMPACT OF TECHNOLOGIES ON THE BUSINESS: A CASE STUDY OF HUAWEI - Yajid, Mohd Shukri Ab; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
Huawei Technologies established in 1988 and headquartered in Shenzhen, China, specializes in the research and development, production and marketing of telecom equipment, providing customized network solutions in different telecom fields. In 2004, Huawei’s contract sales reached USD5.58 billion. Along with the rapid development, Huawei has faced some emerging problems, especially in the high rate problem of employee turnover. A study was undertaken to determine the reasons why workers have the desire to remain employed by an organization. The researcher endeavored to discover those other types of satisfaction that are most often sought by employees regardless of sex, race, education or economic status. If people seek more than pure economic reward from the working environment, it might then be possible to create a profile that could be used to reduce or eliminate undesired employee turnover.